Kepemimpinan Transformasional Dan Transaksional Berdasar Nilai Ajaran Astha Brata - Yanuar Bagas Arwansyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to describe the integration of the values of Astha Brata's teachings in Raden Ngabei Ranggawarsita's Serat Aji Pamasa in the transformational and transactional leadership styles of modern society. The research method uses descriptive qualitative by conducting a literature review of previous research to analyze the application of leadership and transformational styles in five institutions or companies in Indonesia. The results of the analysis are then adjusted to the eight elements contained in the teachings of Astha Brata so that qualitative data can be obtained relating to the suitability of transformational and transactional leadership styles with the values of Astha Brata teachings. The results of this study indicate that there is an integration of astha brata teachings in transformational and transactional leadership styles in various companies. The leaders of institutions or companies prioritize human values in determining the rules of working hours, wages, work targets, rewards, and punishments. In addition, in the application of transformational and transactional leadership styles a leader acts as an example and does not just provide an example. This research can be used as a reference in applying transformational and transactional leadership styles in modern society while still prioritizing the noble values of the previous leaders through the teachings of Astha Brata.